2014
DOI: 10.1038/nmat4153
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity above 100 K in single-layer FeSe films on doped SrTiO3

Abstract: Search for superconductors with a T c above the liquid nitrogen temperature (77 K) led to the discovery of a high-T c cuprate with a T c above 130 K over two decades ago 16 . Even though the value of T c is only 26 K in the first Fe-based superconductor, LaFeAsO (ref. 17) with the earlier work on superconducting oxides interfaces [3][4][5][6] , demonstrates that interface between two different materials provide not only a rich system for studying two-dimensional (2D) superconductivity, but also a potential pat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
843
6
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 1,059 publications
(890 citation statements)
references
References 23 publications
12
843
6
7
Order By: Relevance
“…In contrast to irregular bumps observed in Fig. 1(b), the 1-UC FeSe films on insulating STO exhibit nearly ordered stripes with periods consistent with the 6 × 1 and 5 × 1 reconstructions of STO (110) [1][2][3][4][5][6][7][8][9][10] direction, whereas an one-to-one correspondence between FeSe and STO exists along the [001] direction. It is worth noting that either irregular bumps ( Fig.…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…In contrast to irregular bumps observed in Fig. 1(b), the 1-UC FeSe films on insulating STO exhibit nearly ordered stripes with periods consistent with the 6 × 1 and 5 × 1 reconstructions of STO (110) [1][2][3][4][5][6][7][8][9][10] direction, whereas an one-to-one correspondence between FeSe and STO exists along the [001] direction. It is worth noting that either irregular bumps ( Fig.…”
mentioning
confidence: 65%
“…The single unit cell (UC) films of FeSe on perovskite SrTiO3(STO)(001) substrate (referred as FeSe/STO(001) hereafter) exhibits probably the highest superconducting transition temperature TC [1][2][3][4][5][6][7][8] among all heterostructure systems discovered so far. A superconducting gap of 20 meV 1 , almost one order of magnitude larger than that of bulk FeSe 9 , was observed by scanning tunneling microscopy (STM).…”
mentioning
confidence: 99%
“…6 as a function of d. 1,7,8,10,11,[13][14][15]17,19,20,[23][24][25][26][27] As for the origin of the decrease in T c at d > 9 Å, it may be due to the decrease of the interlayer coupling of cooper pairs. Considering the superconductivity above 100 K in single-layer FeSe films as mentioned above, 6) however, this may be incorrect. According to the prediction by Guterding et al, 18) …”
Section: (B) and (C)mentioning
confidence: 99%
“…Moreover, a superconducting transition has been detected at a high temperature above 100 K in the electrical transport measurements of the single-layer FeSe film. 6) These results suggest that T c of FeSe is very sensitive to the lattice and that FeSe has a great potential in achieving high T c 's. Through the intercalation of potassium 7) and sodium 8) into FeSe, in fact, the interlayer spacing between neighboring Fe layers, d, has increased from 5.52 Å to 7.02 Å and 6.83 Å, so that T c has increased up to ~ 31 K and ~ 37 K, respectively, while T c of lithium-intercalated FeSe without increase in d has remained 8 K. 9) Further increase in d has been attained through the co-intercalation of alkali or alkaline-earth metals and ammonia, so that d and T c have increased to 7 -11 Å and 31 -46 K in A x (NH 3 ) y Fe 2-z Se 2 (A: alkali or alkaline-earth metals), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Exploiting interactions between electrons in one layered material and phonons in an adjacent material could enable new ways to control electron-phonon coupling and realize novel quantum behaviour that has not previously been possible. For example, it has been recently shown that electrons in monolayer FeSe can couple strongly with phonons in the adjacent SrTiO 3 substrate, which may play an important role in the anomalously high critical temperature for superconductivity in the system 21,22 . However, the unusual interlayer electron-phonon interactions in the van der Waals heterostructures have been little explored so far, although there have been indications that interlayer interactions between graphene electrons and the substrate phonons is a limiting factor for higher graphene electron mobility at room temperature 23,24 .…”
mentioning
confidence: 99%